Heart rate variability in elite hockey players of 11-13 years old and selection efficiency in professional youth hockey - Surina-Marysheva, E. F.; Erlkih, V. V.; Korableva, Y. B.; Kantyukov, S. A.; Ermolaeva, E. N. (Journal of Physical Education and Sport, 2018)
The aim of this article is to study the peculiarities of heart rate variability (HRV) in elite hockey players aged 11-13 in terms of efficient selection in youth ice hockey. The study involved 37 elite hockey players aged 11-12 (n=17) and 13 (n=20) years. The standard methods of HRV assessment were used (statistical methods and spectral component). In addition, the method of variation pulsometry and the reactivity index of the parasympathetic nervous system (30:15) were applied. Selection efficiency in youth ice hockey was estimated using the youth league ranking, which is comprised of players in the first year after sport schools (aged 17-18). In hockey players aged 11-12 there was no connection between the parameters of heart rate variability and the league rank, where young athletes played after sport schools. In 13-year hockey players there is a strong direct correlation between RMSSD (r=0.95), ÀÌî% (-0.59) and vegetative rhythm index (VRI) (-0.64). Therefore, HRV regulation in hockey players aged 11-12 is characterized by the absence of stress because of the dominance of parasympathetic influence on sinus node, which corresponds to age-related changes. Heart rhythm regulation in 13-year hockey players is accompanied by stress as a result of the increased influence of central mechanisms regulation under specific physical loads. Such indicators as RMSSD, ÀÌî%, and VRI are important at the beginning of adolescence (13 years) for the assessment of selection efficiency in 11-13-year hockey players.